2018
DOI: 10.1080/10669817.2018.1456028
|View full text |Cite
|
Sign up to set email alerts
|

The application of Mechanical Diagnosis and Therapy to the ankle-foot complex: a case series

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Research has shown Derangement syndrome to closely parallel, or mimic, the patho-anatomical diagnoses lateral epicondylalgia [8], knee osteoarthritis [6], knee meniscus tear [9], shoulder rotator cuff tear [10][11][12], type 2 superior labrum anterior and posterior (SLAP) lesion [11], impingement of the acromioclavicular joint [11,12], de Quervain's disease [13], temporomandibular joint dysfunction [14], and ankle sprain, posterior tibialis tendonitis, plantar fasciitis, and metatarsophalangeal edema [15]. However, Derangement syndrome has a distinct management strategy that focuses on movement based classification, intervention, and prognosis as opposed to a patho-anatomical diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown Derangement syndrome to closely parallel, or mimic, the patho-anatomical diagnoses lateral epicondylalgia [8], knee osteoarthritis [6], knee meniscus tear [9], shoulder rotator cuff tear [10][11][12], type 2 superior labrum anterior and posterior (SLAP) lesion [11], impingement of the acromioclavicular joint [11,12], de Quervain's disease [13], temporomandibular joint dysfunction [14], and ankle sprain, posterior tibialis tendonitis, plantar fasciitis, and metatarsophalangeal edema [15]. However, Derangement syndrome has a distinct management strategy that focuses on movement based classification, intervention, and prognosis as opposed to a patho-anatomical diagnosis [8].…”
Section: Introductionmentioning
confidence: 99%